2013
DOI: 10.1111/2049-632x.12083
|View full text |Cite
|
Sign up to set email alerts
|

Alterations inTLRsas new molecular markers of congenital infections withHuman cytomegalovirus?

Abstract: Toll-like receptors (TLRs) play a crucial role in non-specific immunity against various infections. The most common intrauterine infection, caused by Human cytomegalovirus (HCMV), results in perinatal morbidity and mortality of primary infected fetuses. The induction of immune response by TLRs was observed in HCMV infections in murine models and cell lines cultured in vitro. Studies reported an immunological response in pregnant women with primary HCMV infection and TLR2 activity in collecting of HCMV particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 148 publications
(252 reference statements)
0
20
0
Order By: Relevance
“…For instance, TLR2 was been found to functionally recognize HCMV through direct interaction with the envelope tegumental glycoproteins, gB and gH, suggesting that the innate immune response activated by HCMV might be primarily dependent on viral envelope proteins and independent of viral replication in permissive fibroblasts [76]. Moreover, there was a reported interaction of CMV with TLR7 and TLR9 in human plasmacytoid dendritic cells (pDC), suggesting that TLR involvement might also be related to the cell types in which the virus establishes the infection [77]. The downregulation of TLR signaling pathways may help CMV infect pDCs and transfer to endothelial cells and fibroblast during early infection, while activation of TLRs in these cells may increase during viral reactivation at a later stage contributing to SSc disease.…”
Section: Cytomegalovirus Innate Immunity Vasculopathies and Fibrosmentioning
confidence: 99%
“…For instance, TLR2 was been found to functionally recognize HCMV through direct interaction with the envelope tegumental glycoproteins, gB and gH, suggesting that the innate immune response activated by HCMV might be primarily dependent on viral envelope proteins and independent of viral replication in permissive fibroblasts [76]. Moreover, there was a reported interaction of CMV with TLR7 and TLR9 in human plasmacytoid dendritic cells (pDC), suggesting that TLR involvement might also be related to the cell types in which the virus establishes the infection [77]. The downregulation of TLR signaling pathways may help CMV infect pDCs and transfer to endothelial cells and fibroblast during early infection, while activation of TLRs in these cells may increase during viral reactivation at a later stage contributing to SSc disease.…”
Section: Cytomegalovirus Innate Immunity Vasculopathies and Fibrosmentioning
confidence: 99%
“…The identified heterozygotes in the range of TLR2 SNP were estimated as 10 times more susceptible to develop the infection. TLR2 molecule was previously reported to be involved in the immune response against HCMV [15, 1921]. In ectocervical tissue, HCMV infection was blocked by ligands for TLR2 (LTA), as well as TLR9 (CpG) molecules [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported some involvement of Toll-like receptors (TLRs) in immune response against HCMV [1315]. Particularly, the TLR2 molecule was shown to support the immunity to the virus [1618].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphisms in TLR2 appear to enhance an individual's susceptibility to lytic infection and the development of subsequent pathology [162]. Other authors have reported that TLR polymorphisms or epigenetic changes in the methylation state of their gene promoter regions influence the duration and magnitude of the immune response to HCMV infection [163]. On the other hand, heterozygosity in TLR2 and TLR4 receptors diminishes the risk of infection by this virus in adults [164].…”
Section: Cytomegalovirusmentioning
confidence: 99%